Plant Nucleases: III. Polyacrylamide Gel Electrophoresis of Corn Ribonuclease Isoenzymes - Wilson, Curtis M. (1971)
Isoenzymes of RNase were detected in plant extracts after polyacrylamide gel electrophoresis with a new buffer system. The gels were incubated in an RNA solution, then dipped for 30 seconds into 0.2% toluidine blue. The method is rapid and is sensitive to very small amounts of RNase. The effects of buffers and ethylenediaminetetraacetate on the different enzymes are illustrated by photographs and scans of the gels. RNase I, from endosperms and roots, was the fastest-moving corn RNase. Two isoenzymes of corn RNase II, from microsomes, were detected in the hybrid WF9 × M14, while each parental inbred had one of the isoenzymes. Three isoenzymes of corn Nuclease I, from crude mitochondria, had about the same mobility as the RNase II isoenzymes, but were inhibited by ethylenediaminetetraacetate. RNases were also detected in tobacco and wild carrot tissue cultures.